Bone suture and lateral sinus lift surgery - Amin Rahpeyma; Saeedeh Khajehahmadi (Wolters Kluwer Medknow Publications, 2015)
Bone suture in lateral sinus lift has four indications. Three of them depend on creating a hole in the lateral maxillary sinus wall above the antrostomy window for securing the elevated medial maxillary sinus membrane to manage perforated Schneiderian membrane. Covering the buccal antrostomy window with the buccal fat pad (BFP) for better nourishment of the inserted graft and as an alternative for bone tags in fixation of collagen membrane has been reported previously. A new indication for firmly anchoring the BFP to the medial maxillary sinus wall as the last resort for the management of perforated Schneiderian membrane is explained in this article.